2020
DOI: 10.1021/acs.analchem.9b04617
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Flow-Injection Analysis of Phenols Induced by Reactive Oxygen Species Generated under Daylight Irradiation of Titania Impregnated with Horseradish Peroxidase

Abstract: Titanium dioxide (TiO2) is a unique material for biosensing applications due to its capability of hosting enzymes. For the first time, we show that TiO2 can accumulate reactive oxygen species (ROS) under daylight irradiation and can support the catalytic cycle of horseradish peroxidase (HRP) without the need of H2O2 to be present in the solution. Phenolic compounds, such as hydroquinone (HQ) and 4-aminophenol (4-AP), were detected amperometrically in flow-injection analysis (FIA) mode via the use of an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…The collection of UV absorption curves (Figure S1) confirmed that the catalytical oxidation of OPD to DAP with a typical absorption peak at 417 nm induced the emission not from the generation of the Cu­(OPD) 2 2+ complexes, which exhibited an absorption peak at 438 nm . The emission from DAP based on the catalytical oxidation in the presence of Cu 2+ was similar to that using horseradish peroxidase or enzyme mimics . Furthermore, the emission was dependent on the concentration of Cu 2+ (Figure A).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The collection of UV absorption curves (Figure S1) confirmed that the catalytical oxidation of OPD to DAP with a typical absorption peak at 417 nm induced the emission not from the generation of the Cu­(OPD) 2 2+ complexes, which exhibited an absorption peak at 438 nm . The emission from DAP based on the catalytical oxidation in the presence of Cu 2+ was similar to that using horseradish peroxidase or enzyme mimics . Furthermore, the emission was dependent on the concentration of Cu 2+ (Figure A).…”
Section: Resultssupporting
confidence: 52%
“…26 The emission from DAP based on the catalytical oxidation in the presence of Cu 2+ was similar to that using horseradish peroxidase or enzyme mimics. 27 Furthermore, the emission was dependent on the concentration of Cu 2+ (Figure 1A). Then, PTA-NH 2 as the donor was introduced to the above OPD-Cu 2+ system.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The amino group was an electron-donating group when located in ortho and counter position. It attached to the benzene ring with an unshared electron pair led to p-π hyper conjugation on the benzene ring and increased the density of the electron cloud on the aromatic ring ( Maity et al, 2020 ; Rahemi et al, 2020 ). Thus, this could help to explain why MPD and PEI did not produce fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The applications can be seen for organic analytes such as organophosphate insecticides, 173 ascorbic acid, 2,3-dihydroxybenzoic acid and pyrocatechol 174 and phenol. 175 Applications of inorganic analyte detected by amperometric flow-based system are chlorine, 176 heavy metals (Pb(II), Cd(II) and Cu(II)), 177 manganese 178 and arsenic. 179 Potentiometric detection can be observed for ion-selective sensors.…”
Section: Application Of Flow-based System For Environmental Monitoringmentioning
confidence: 99%